Abnormal hemoglobin variants, ABO, and Rhesus blood group distribution among students in the Niger Delta of Nigeria - O Erhabor; TC Adias; Z A Jeremiah; et al (Dove Medical Press, 2010)
O Erhabor1, TC Adias2, Z A Jeremiah1, M L Hart21Department of Medical Laboratory Sciences, College of Health Sciences, Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria; 2Department of Medical Laboratory Sciences, Rivers State University of Science and Technology, Port Harcourt, NigeriaBackground: Communities in Africa constitute a major part of the population that is vulnerable to many erythrocytic hereditary and hematological disorders such as hemoglobinopathies. The frequencies of abnormal hemoglobin variants, ABO, and Rhesus blood groups vary from one population to another.Methods: The aim of this study was to find the prevalence/spectrum of hemoglobin variants, ABO, and Rhesus blood group distribution among 204 undergraduate students of African descent in Port Harcourt in the heart of the Niger Delta geopolitical zone of Nigeria. Standard alkaline cellulose acetate electrophoretic technique using the Shandon electrophoretic tank with tris-ethylene diamine tetracetic acid (EDTA) borate buffer and hemagglutination techniques were employed for the determination of abnormal hemoglobin variants, ABO and Rhesus blood groups, respectively. Results: Two hundred and four apparently healthy students of African descent comprising 124 males (60.8%) and 80 (39.2%) females with a mean age 24.5 ± 6.5 years took part in the study. Subjects were screened for abnormal hemoglobin variants, ABO, and Rhesus groups. Normal hemoglobin accounted for 69.1%, followed by abnormal sickle cell trait in 29.4%, and the sickle cell disease in 1.5% of the study population. The distribution of the various blood groups indicated that 46% were blood group O, 26.6% were group A, 23.6% were group B while 3.8% were group AB. Rhesus (RhD) positivity rate was 93% while RhD negativity accounted for 7%.Conclusion: This research indicates a high prevalence of hemoglobin variants in the study population. Carrier screening and mutation identification can become the cornerstones of any prevention program for hemoglobin disorders. It can also help in the formulation of genetic counseling policies to help prospective couples make informed decisions in a bid to reduce the sickling gene pool in the Niger Delta of Nigeria.Keywords: abnormal hemoglobin variants, ABO, Rhesus blood group, Niger Delta, Nigeria